2016
DOI: 10.1007/s11356-015-6002-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal uptake of Nerium oleander from aerial and underground organs and its use as a biomonitoring tool for airborne metallic pollution in cities

Abstract: The analysis of the airborne particulate matter-PM-incorporated to plant leaves may be informative of the air pollution in the surroundings, allowing their use as biomonitoring tools. Regarding metals, their accumulation in leaves can be the result of both atmospheric incorporation of metallic PM on aboveground plant organs and root uptake of soluble metals. In this study, the use of Nerium oleander leaves as a biomonitoring tool for metallic airborne pollution has been assessed. The metal uptake in N. oleande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It is well known that N. oleander is an ornamental plant that can be adapted to extreme drought and other stressors, and is widely selected in phytoremediation applications, since it reduces HMs from various matrices through phytoaccumulation and phytostabilization. This has been confirmed by several studies in the literature, indicating that N. oleander is a suitable plant species for biomonitoring of heavy metal pollution [ 46 , 47 , 48 , 49 , 50 ]. It is clear that each metal has a different uptake mechanism, which is also influenced by the soil characteristics.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is well known that N. oleander is an ornamental plant that can be adapted to extreme drought and other stressors, and is widely selected in phytoremediation applications, since it reduces HMs from various matrices through phytoaccumulation and phytostabilization. This has been confirmed by several studies in the literature, indicating that N. oleander is a suitable plant species for biomonitoring of heavy metal pollution [ 46 , 47 , 48 , 49 , 50 ]. It is clear that each metal has a different uptake mechanism, which is also influenced by the soil characteristics.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, it is important to note any study focusing on arsenic (As) phytoremediation, since As belongs to the same group of the periodic table (15) as antimony and they share similar chemical properties. It was reported that the translocation factor and the bioaccumulation values of As in N. oleander are 0.51 ± 0.25 and 0.13 ± 0.01, respectively, at an initial arsenic dose of 100 μM [ 49 ]. In our experiments, the Sb concentration in the roots was higher than in the above ground part for all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…(5) allow a higher density of sampling sites; and (6) allow an accessible approach for the analytical determination of trace elements [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of MTE accumulation at Bir Hadada is presumably not only linked to a large number of quarries, but also related emissions from intensive agricultural operations which degrade the environment through the release of pesticides and chemicals that generate associated toxic heavy metal particles suspended in the environment (Wei and Yang. 2010;Vázquez et al 2016;Kirpik et al 2017;Oumenskou et al 2018).…”
Section: Discussionmentioning
confidence: 99%